Stacking Effects in van der Waals Heterostructures of Silicene and Hexagonal Boron Nitride. Issue 11 (23rd August 2018) - Sattar, Shahid; Zhang, Yongyou; Schwingenschlögl, Udo
Abstract: The stacking effects on the electronic structure of van der Waals heterostructures consisting of silicene and hexagonal boron nitride are investigated by first‐principles calculations. It is shown that the stacking is fundamental for the details of the dispersion relation in the vicinity of the Fermi energy (gapped, non‐gapped, linear, parabolic) despite small differences in the total energy. It is also demonstrated that the tight‐binding model of bilayer graphene is able to capture most of these features of the van der Waals heterostructures, and the limitations of the model are identified. Abstract : Here, the electronic properties of vertically stacked van der Waals heterostructures of silicene and hexagonal boron nitride are studied by means of first‐principles calculations. An effective Hamiltonian approach is used to quantify the onsite energies and interlayer couplings. The findings provide general insights into stacking effects on the electronic states of buckled two‐dimensional systems.